Polarization model of thermal contrast observation objects - Kolobrodov, V.G.; Mykytenko, V.I.; Tymchyk, G.S. (Journal of Thermoelectricity, 2020)
This paper proposes a polarization model of a thermal imager for the purpose of its application in the study of thermoelectric phenomena and devices, which allows increasing the efficiency of such devices. To study and design such thermal imagers, a physico-mathematical model of polarization of radiation from observation objects is considered, which takes into account the polarization properties of the intrinsic thermal radiation and the reflected external radiation. The developed model was used to determine the polarization properties of the radiation from a flat iron plate. The analysis of the obtained results shows that for thermal radiation at observation angles ψ <40 ° the components of the radiation coefficient are almost identical ε∥≈ε⊥≈0.16, but ε∥ <ε⊥. As the observation angle ψ <40 ° increases, the perpendicular polarization component ε⊥ decreases monotonically to zero, and the parallel component ε∥ increases and reaches its maximum value at an angle ψ = 84 °, and then decreases to zero. The degree of polarization of radiation increases with increasing angle ψ and at an angle ψ = 84 ° is equal to 0.96. The obtained research results are worthwhile to be used in the development of a model of thermoelectrics which can be employed in the design of a polarization thermal imager. Bibl. 8, Tabl. 1, Fig. 7.